PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMPN 3 TALAMAU - Roza, Melia (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) STKIP Ahlussunnah, 2020)
The ability of mathematical communication is one of the goals of mathematics learning so that this ability is expected to grow and experience improvement. However, it was found that the communication skills of grade VIII students at SMPN 1 Bonjol were still low. Based on the results of observation can be concluded that the cause is the learning model used has not been able to enable students in the learning process. So that the learning process has not been able to develop students' mathematical communication skills. One of the learning model that can develop students' mathematical communication ability is cooperative learning model Think Talk Write (TTW). The purpose of this study is to determine whether the mathematical communication skills of students with the application of cooperative learning model Think Talk Write (TTW) is better than the mathematical communication ability of the control class students. The type of this research is experimental research with Randomized Subjects Posttest Only Control Group Design. Population in this research is student of class VIII SMPN 3 Talamau. The sample of the research is students of class VIII.1 and VIII.2 SMPN 3 Talamau. Based on the result of the research, it can be concluded that students' mathematical communication ability by applying cooperative learning model Think Talk Write (TTW) is better than mathematical communication ability of students with conventional learning.